Descriptions of three South American genera of Euliini and five their species (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two genera (Crocotania and Sinxema) and four new species (C. crocota, S. xenisma, S. chapada, Galomecalpa empirica) are described from Ecuador. Galomecalpa secunda is redescribed and the key to the identification of Galomecalpa is provided.